An anisotropic cohesive fracture model: Advantages and limitations of length-scale insensitive phase-field damage models. (15th February 2022) - Rezaei, Shahed; Harandi, Ali; Brepols, Tim; Reese, Stefanie
Abstract: The goal of the current work is to explore direction-dependent damage initiation and propagation within an arbitrary anisotropic solid. In particular, we aim at developing anisotropic cohesive phase-field (PF) damage models by extending the idea introduced in Rezaei et al. (2021) for direction-dependent fracture energy and also anisotropic PF damage models based on structural tensors. The cohesive PF damage formulation used in the current contribution is motivated by the works of Lorentz et al. (2011), Wu and Nguyen (2018) and Geelen et al. (2019). The results of the such models are shown to be insensitive with respect to the length scale parameter for the isotropic case. This is because they manage to formulate the fracture energy as a function of diffuse displacement jumps in the localized damaged zone. In the present paper, we discuss numerical examples and details on finite element implementations where the fracture energy, as well as the material strength, are introduced as an arbitrary function of the crack direction. Using the current formulation for anisotropic cohesive fracture, the obtained results are converging with respect to the length scale parameter. This is achieved by including the direction-dependent strength of the material in addition to its fracture energy. Utilizing the current formulation, one can increase the mesh size which reduces the computational time significantly without any severe change in the predicted crack path and overall obtained load–displacement curves. We also argue that these models still lack to capture mode-dependent fracture properties. Open issues and possible remedies for future developments are finally discussed as well. Highlights: Direction-dependent strength and toughness are considered in the cohesive CPF model Numerical examples show the potential of the unified model for bulk and interface The results of the anisotropic model converge regarding the length scale parameter Using the CPF model, one can increase the mesh size and reduce the computational cost We argue that these models still lack to capture mode-dependent fracture properties.